The Influence of Economic and Entrepreneurial Environmental Factors on Coffee Farming Performance in Banyuwangi Regency - Yusmia Widiastuti (Journal of Aquaculture Science, 2021)
The plantation sector is a sector that plays a role in the country's foreign exchange earnings. One of the foreign exchange-producing plantation commodities is coffee. In 2011, foreign exchange earnings from coffee commodities resulted in an export value of US$ 1,085.89 million or 10.1% of the export value of all agricultural commodities, or 0.5% of non-oil and gas exports or 0.4% of the total export value. To increase coffee productivity both in quality and quantity, it is necessary to improve the economic environment and also have the entrepreneurial competence of coffee farmers. The purpose of this study was to analyze the influence of the economic environment and entrepreneurship on-farm performance. This research was carried out in Banyuwangi Regency which was carried out purposively with the research population being coffee farmers who had a coffee area of 0.5 - 1 Ha. The results of the study show that the economic environment has a positive effect on entrepreneurship as a result, the better the economic environment, the better the entrepreneurship of farmers. The economic environment does not directly affect the performance of coffee farming but has a direct effect on farmer entrepreneurship. Entrepreneurship has a positive effect on farm performance, as a result, the better the farmer's entrepreneurship, the better his farming performance. Keywords: Economic Environmental Factors, Entrepreneurship, Farming Performance, Coffee